Trend of NFC Technology for Payment Transaction - Edi Purnomo Putra; Fifilia Fifilia; Hanny Juwitasary (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2018)
Implementation of NFC Technology was developed to facilitate instant payment transaction such as purchase tickets, goods, or service to become one of the digital wallet besides to using credit cards. The high rate of mobile devices usage in Indonesia make many companies take advantage of this device as a media in electronic payment transactions, a lot of banking and financial product in Indonesia used this technology such as E-money, T-cash, Flazz, Ooredoo, Dompetku, XL-Tunaiku, Doku Wallet, Skye card, Artajasa MYNT and many more. The technique that used in this research to prove the hypotheses was Structural Equation Model (SEM) using Smart PLS software, we will used questionnaire and literature review method to found trend of NFC use. The population from which to draw conclusion was defined as all individual capable use NFC Technology for payment transaction .In this study, we will investigate NFC use in Indonesia, The proposed research model was develop by TAM Framework with some dimension from NFC study iterature that is Mobile Payment Knowledge, Technology, Trust, Behaviour and Compatibility into the model, in order to determine the significant factor that influence of NFC use in Indonesia.